Reflective thinking and its relationship to the accuracy of court defense skills in female volleyball - Amir, Prof. Dr. Hamida Obaid Abdul; Ali, Asst.Prof.Dr. Majida Abbas Muhammad; Mohamed, Asst.L. Gihan Khairy (Sulaimani Journal for Humanities, 2026)
Volleyball is a team sport that has achieved prominence in terms of its popularity and widespread practice across the globe. The game is distinguished by its inclusion of numerous fundamental offensive and defensive skills, which are crucial pillars upon which the game is built. A student's success depends on mastering these skills. Court defense is a key and essential skill in volleyball, as it is a key to scoring points for the team. Mastering this skill requires both theoretical and practical application, along with addressing the challenges that often accompany it. These challenges typically consume a significant portion of the lesson plan or demand considerable effort and thought from the student. Hence, the importance of researching reflective thinking and its relationship to court defense skills in female volleyball. Therefore, most educators, across various schools of thought and perspectives, agree on a fundamental principle and important strategic goal: to help the vast majority of students reach a high level of learning and improve their performance. The research problem can be summarized in the following question: What is the relationship between reflective thinking and court defense skills in female volleyball? One of the main objectives of this research is to identify reflective thinking and its relationship to female students' court defense skills in volleyball. The research hypothesis posits a direct correlation between reflective thinking and court defense skills in volleyball. In Chapter Two, the researchers outlined the procedures for administering the reflective thinking scale and assessing court defense skills in volleyball. Chapter Three presented and discussed the results. The most significant conclusion was the emergence of a statistically significant correlation between reflective thinking and the accuracy of court defense skills in volleyball. The key recommendations included focusing on developing reflective thinking skills in female students' volleyball performance and encouraging teachers to calm students before competitions to improve their psychological state, morale, and reflective thinking abilities.